Large dams, energy justice and the divergence between international, national and local developmental needs and priorities in the global South. (July 2018) - Siciliano, Giuseppina; Urban, Frauke; Tan-Mullins, May; Mohan, Giles
Abstract: This paper investigates from a socio-technical and energy justice perspective the lack of coordination of international, national and local developmental priorities and inclusion of local needs in the decision making process of large dam construction in the global South. The paper argues that the analysis of energy infrastructures as socio-technical systems requires an energy justice approach to capture the true environmental and social nature of energy production and consumption. In doing so, this paper proposes a conceptual framework called "The Energy Justice Framework for Dam Decision-Making" as a tool to inform energy decisions on infrastructure development based on energy justice principles and social impact assessment. The proposed framework is used in this paper to analyse distributional, procedural, restorative justice, and power relations throughout the entire dams' energy system in the case of four large dams located in Africa and Asia, namely Kamchay dam in Cambodia, Bakun dam in Malaysia, Bui dam in Ghana and the planned Zamfara dam in Nigeria.